Differential impact of antiepileptic drugs on the effects of contraceptive methods on seizures: Interim findings of the epilepsy birth control registry. (May 2015) - Herzog, Andrew G.
Highlights: Epilepsy Birth Control Registry (EBCR) is a web based survey and educational site. EBCR collects data regarding contraception practices of women with epilepsy. Changes in seizures are more common with hormonal than non-hormonal contraception. Seizure increase is more common than seizure decrease with hormonal contraception. Seizure increase on hormonal contraception appears highest on valproate. Abstract: Purpose: To present the interim findings of the Epilepsy Birth Control Registry (EBCR) regarding the impact of various contraceptive methods on seizures, stratified by antiepileptic drug (AED) type. Methods: This is an observational study that reports interim findings on the first 750 subjects. Results: There are significantly greater relative risks (RR) for both seizure increase and decrease with hormonal contraception (HC) than with non-hormonal contraception (NHC). The rates of HC experiences associated with seizure increase (21.0%) are greater than with NHC (3.9%) (RR = 5.39 [95% CI = 3.77–7.73, p < 0.0001]). The rates of HC experiences associated with seizure decrease (10.3%) are greater than with NHC (5.6%) (RR = 1.85 [95% CI = 1.30–2.62, p = 0.0006]). While differences can reflect biological effects or reporting bias, the finding of a greater RR for seizure increase with hormonal patch than with combined oral contraceptive, perhaps related to the delivery of substantially higher concentrations of hormones, and a greater RR for seizure decrease with depomedroxyprogesterone, known to reduce seizure frequency when used in dosages which produce amenorrhea, support biological effects. All AED categories showed significantly higher frequencies of reports of seizure increase when combined with HC than with NHC. RR for seizure increase with HC was higher with valproate than with any other AED category. There were no significant differences among AEDs for seizure decrease with HC at this juncture of the study. Overall, NEIAEDs had the most favorable profile with regard to reports of seizure increase and decrease when used with HC. Conclusions: Interim EBCR findings suggest that contraception category and interactions between contraception category and AED category are predictive factors for changes in seizure frequency in WWE.